2011
DOI: 10.1007/s10695-011-9473-4
|View full text |Cite
|
Sign up to set email alerts
|

Cortisol response to air exposure in Solea senegalensis post-larvae is affected by dietary arachidonic acid-to-eicosapentaenoic acid ratio

Abstract: An experiment was conducted in order to evaluate the effects of feeding frozen Artemia diets differing in arachidonic acid-to-eicosapentaenoic acid ratios (ARA/EPA) on growth, survival and stress coping ability of Senegalese sole post-larvae (19-31 days after hatch). Two experimental diets presenting high ('High'; 3.0) or low ('Low'; 0.7) ARA/EPA ratios were tested under two rearing conditions: undisturbed (C) and stressed by a 2-min air exposure every two days (S). Growth, survival and basal cortisol levels w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 40 publications
1
17
0
Order By: Relevance
“…Similarly, whereas the cortisol response of cobia fed the 12% FM and 12% PL + Soy PL feeds was heightened relative to fish fed the 50% FM feed, the response of fish fed the 12% FM + Marine PL feed was intermediate between these groups. The importance of dietary phospholipid content in ensuring proper growth and development during early life history of fishes has been well-reviewed (Cotteau et al, 1997;Tocher et al, 2008;Cahu et al, 2009;Alves Martins et al, 2011), and cobia are known to require significant amounts of phospholipid during ontogeny. Niu et al (2008) observed that increasing dietary phospholipid increased growth and survival of advanced cobia larvae (initial weight = 0.4 g), ultimately concluding that the phospholipid requirement of this species may exceed 8% of the diet.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, whereas the cortisol response of cobia fed the 12% FM and 12% PL + Soy PL feeds was heightened relative to fish fed the 50% FM feed, the response of fish fed the 12% FM + Marine PL feed was intermediate between these groups. The importance of dietary phospholipid content in ensuring proper growth and development during early life history of fishes has been well-reviewed (Cotteau et al, 1997;Tocher et al, 2008;Cahu et al, 2009;Alves Martins et al, 2011), and cobia are known to require significant amounts of phospholipid during ontogeny. Niu et al (2008) observed that increasing dietary phospholipid increased growth and survival of advanced cobia larvae (initial weight = 0.4 g), ultimately concluding that the phospholipid requirement of this species may exceed 8% of the diet.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary effects, in particular the effect of ARA/EPA ratio, in the stress response of this species have also been investigated by Alves-Martins et al (2011). These authors observed a quicker recovery from an air exposure acute stress, but not from a repeated stress (determined as the return of cortisol to basal levels) when postlarvae were fed a low ARA/EPA ratio (0.7).…”
Section: Stress Responsementioning
confidence: 99%
“…Montero et al [ 15 ] detected higher levels of cortisol in gilthead sea bream submitted to a stress induced by high stock density and fed a diet with 60 and 80% of FO substituted by lindseed oil. Furthermore, Alves-Martins et al [ 77 , 78 ] reported increased levels of basal cortisol related to high contents of arachidonic acid (ARA) in the diet of Senegalese sole larvae. However, when dietary FO is substituted by a blend of vegetable oils and a balanced n-3 to n-6 LC-PUFA ratio is provided in the diet, no differences are found with respect to diets based on FO and even some stress effects can be prevented [ 16 , 79 ].…”
Section: Discussionmentioning
confidence: 99%